Cisplatin-Etoposide Induced Myocardial Infarction in a Patient with Small Cell Carcinoma - Srija Katta, Sheetal Chauhan, Ajit Singh, Prasad N. Shetty, Hashir Kareem, Tom Devasia (Journal of Applied Pharmaceutical Science, 2018)
Various drugs used to treat cancer cause hemodynamic/physiological changes in various organs of the body. Cardiotoxicity is one of the major side effects. Cardiotoxicity associated with chemotherapy can range from asymptomatic sub-clinical echocardiographic changes to life-threatening events like congestive heart failure or acute coronary syndrome. We present a case of cisplatin and etoposide-induced myocardial infarction (MI) during the second cycle of chemotherapy for bronchogenic carcinoma of the left lung (small cell carcinoma). The patient developed troponin positive NSTEMI and was managed conservatively. Here, the possible mechanism of action and the importance of cardiac screening while using cisplatin and etoposide are discussed.
Keywords: Chemotherapy-induced Cardiotoxicity,Anthracycline,Bronchogenic carcinoma,Antineoplastic drugs.